Perlindungan Hukum atas Hak Kekayaan Intelektual Komunitas Band di Kabupaten Merauke - Fahmi, Muhammad Saiful; Klau, Ricardo Goncalves; Rado, Rudini Hasyim; Majid, Ilham (AHKAM, 2024)
The creative industries have been set by the government as one of the pillars of national economic development, according to OPUS Creative Economy 2020 report, the contribution of the creative economy subsector to the national PDP reached Rs. McKinsey & Company through its research in 2016 stated that Indonesia is becoming one of the four most potential countries for the digital music industry in Asia, revenue or market value of streaming music in Indonesia in 2020 is estimated to reach $148 million or around IDR 2.1 Trillion and the growth rate is expected to reach 6.4 percent by 2024, creating market value around $190 million. One of the forms of music produced by the people in Indonesia and in particular in Merauke district was born from the local community of bands, such as Coffe Break, Kaki Abu, Amandus (Black Lebel One Scout), Jeppo (KANADA), and Anjhas Noya. (No Name Crew). Nevertheless, the potential economic gain cannot be achieved optimally if the importance of legal protection of intellectual property rights (IPR) is disregarded. In general, this research is intended to find out and analyze the extent to which the legal protection of IPR for music/song creations in the Band Community in Merauke district. This research uses the method of empirical juridic research.